La dama de oro - Brühl, Daniel; Mirren, Helen, 1945-; Speak Up (DVD (Speak Up), 2015)
Maria Altmann, an octogenarian Jewish refugee, takes on the Austrian government to recover artwork she believes rightfully belongs to her family.